Multidisciplinary approach and early use of percutaneous mechanical circulatory support devices in patients with cardiogenic shock. (25th November 2020) - Venuti, A; Gramegna, M; Baldetti, L; Calvo, F; Pazzanese, V; Sacchi, S; Cappelletti, M.A
Abstract: Background: Despite progresses in the reperfusion strategies, the prognosis of patients with cardiogenic shock (CS) remains poor with a high in-hospital mortality rate. Percutaneous mechanical circulatory support systems (pMCS) reducing afterload, preload and myocardial oxygen demand, preventing compensatory tachycardia and increasing mean arterial pressure, lead to improve end-organ perfusion. Since CS progression to a refractory shock state is deleterious, timing of treatment represents a crucial issue in these patients. Purpose: The aim of our study was to assess whether a multidisciplinary approach and an early use of pMCS could be safe and effective in improving CS patients' outcome. Methods: We examined the outcome in terms of one-month survival of 62 patients (75.8% males, mean age 67.7±12.2 years) admitted between January and December 2018 to our Cardiac Intensive Care Unit (CICU) with cardiogenic shock due to acute coronary syndrome (ACS), acute heart failure (AHF) and other causes in 43.5%, 21.6%, 35.4% of cases respectively. For each patient, a Multidisciplinary Shock Team (CS-Team) including critical care specialists, interventional cardiologists and advanced heart failure specialists, was involved and the early use of pMCS was considered. Results: Overall, 52 (83.9%) CS patients underwent pMCS implant, including intra-aortic ballon pump counterpulsation (IABP), Impella system (Impella), venous-arterial extracorporeal membrane oxygenation (VA ECMO) in 67.7%, 46.7%, 11.3% of cases respectively. Median time from the first CS-Team contact to the pMCS implantation was 32.5 (30–60) minutes. Among ACS-CS group, AHF-CS group and CS-due to other causes group, pMCS were implanted in 25 (92.5%), 12 (92.3%) and 15 (68.1%) patients respectively. Lower extremities ischemia, gastrointestinal/intracerebral and life-threatening bleeding and ischemic stroke were observed as pMCS related adverse events in 9.7%, 6.4%, 1.6%, 3.2%, 6.4% of cases respectively. At one month, 56 (90.3%) CS patients were discharged alive while 6 (9.7%) CS patients died during the CICU stay. Conclusion: A multidisciplinary approach of CS patients, contemplating an early and extensive use of pMCS, may be effective in the reduction of in-hospital mortality rate with a low and acceptable occurrence of pMCS related adverse events. Funding Acknowledgement: Type of funding source: None